A rendszerváltás választása - Dombi, Péter; Kovács, Dezső (Tér és Társadalom, 1991)
Political distribution created by the 1990 parliamentary elections can be visualized in spatial and settlement dimensions as well. For the first sight, our short description on the spatial aspects of differences is a hind of immaginative political photo album, which facilitates us to follow up the changes on the first shot. The election results showed the support of parties, the different interests and preferencies of voters in the different regions of Hungary. The 1990 elections, the system endeavouring proportionate representation, primarily aimed at creating stabile, multi-party parliamentary democracy. The rules of elections were established by the political élite who created the framework for the transformation, while the delineation of individual constituencies was preceded by party-policy coordinations at county level. Besides others, the election rules of political transition, and the political spheres created for voters will very likely change by the next elections taking the new conditions of power into account. Participation of voters at the elections shows great regional differences. Participation was higher than average in the Western part of Hungary, where population density is higher, and also in the central region. However, participation was lower than average in the Eastern part. At the same time, this difference did not appear within the seftlement network among the settlements, as proportion of people living in settlements with different size was nearly the same at the elections. In harmony with its original purpose, the election system filtered the parties, and only six of them got into the parliament. However, the support of the six parliamentary parties differs by regions, counties and seftlement groups. Social, economic, national, etc. differences of the counties are reflected in the distribution of votes given to different parties. At the 1990 elections, in spite of their similarities in ideology and program, the parties moderately intended to establish coalition. In the background of it, one could reveal the intention that the parties wanted get a clear picture about the number of their voters, which will then give them a legitimate background. Theoretical coalitions created from the election results of parliamentary parties give a somewhat more overall view of the voting behaviour of the inhabitants of certain regions. Results on the governing and oppositional coalition show, that: There are significant regional differences in southern Great Plain in favour of the governing coalition, and in the central region in favour of the opposition; In the seftlement network, at settlements with less than 10,000 inhabitants (in villages), the parties of governing coalition, while at settlements with more than 10,000 inhabitants (in cities) the parties of opposition gained more votes; In the different regions, 15-21% of votes is distributed among the 13 parties which did not get into the parliament (with the exception of central region). It depends on the future political changes, whether these small parties can survive or not. The importance of central region, and the fierce fight among the parliamentary parties is indicated by the fact that the small parties could gain only 9.8 % of all the votes in the central region. Our paper investigated the spatial appearence of the political distribution of Hungarian parliamentary elections from the point of view of votes on parties. In spite of fears and forecasts preceding the elections, the Hungarian voters could chose among the parties, and primarily voted on the party chosen. Their votes on individual nominees were also basically motivated by the choice of party. However, drawing the detailed political map of elections, and determining regional differences and similarities requires further comparative analysis of the distribution of votes in different constituencies and of mandates.